Comparative outcomes of extracorporeal shockwave therapy for shoulder tendinitis or partial tears of the rotator cuff in athletes and non-athletes: Retrospective study. (March 2018) - Chou, Wen-Yi; Wang, Ching-Jen; Wu, Kuan-Ting; Yang, Ya-Ju; Cheng, Jai-Hong; Wang, Shih-Wei
Abstract: Background: Refractory shoulder tendinitis or partial thickness rotator cuff tears (PTRCTs) are common findings in overhead athletes. Previous studies have examined the effectiveness of extracorporeal shockwave therapy (ESWT) for shoulder tendinitis. Materials and methods: In the current study, we recruited 36 shoulders and performed a comparison between the professional athletes (13 shoulders, athletic group; AG) and the non-athletic population (23 shoulders, non-athletic group, NAG) with PTRCTs or shoulder tendinitis of the shoulder after ESWT. Patients with symptomatic tendinitis of the shoulder with or without a partial tear of the rotator cuff tendon and failed oral medication and physical therapy for more than 3 months were treated with electrohydraulic mode of ESWT. All patients that met the inclusion criteria were categorized into two groups according to their pre-treatment activity level. Results: We found that NAG exhibited significant aging and degenerative change around the glenohumeral joint and subacromial space. After ESWT treatment, the patients in AG were with 53.8% high satisfaction rating and patients in NAG were 52.1% by one-year followed up. Conclusion: The results showed ESWT was equally effective treatment in both AG and NAG. In light of its efficacy and less-invasive nature, we suggest ESWT can be used to treat athletes with refractory tendinitis or PTRCTs before proceeding to arthroscopic intervention. Highlights: ESWT is an effective treatment method for shoulder tendinitis. ESWT improve high satisfaction rate in athletes with shoulder tendinitis or PTRCTs. ESWT improve young and aging athletes with shoulder tendinitis or PTRCTs. . ESWT is suggested to treat athletes with refractory tendinitis or PTRCTs.